Kesetaraan Gender dan Inklusi Sosial dalam Membentuk Karakter Religius pada Anak Sekolah Luar Biasa di Jawa Tengah - Fanani, Istiqlal Yul; Wakhidah, Esti Nur; Sulaeman, Muhammad Azka (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the influence of gender equality and social inclusion on the character development of students in Special Education Schools (SLB). The research method used is quantitative, with a sample size of 366 individuals. Data analysis was conducted using SEM PLS. The findings indicate that both gender equality and social inclusion have a significant influence on the character development of SLB students. The implications of these findings emphasize the need for strengthening educational policies focused on equality and social inclusion to ensure that every student, regardless of gender or special needs, has equal opportunities to develop holistically, both academically and morally.